2007
DOI: 10.1016/j.otohns.2006.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of patient‐reported outcome measures in head and neck cancer surgery

Abstract: Rigorous instrument development is important for creating valid, reliable, and responsive disease-specific questionnaires. As a direction for future instrument development, an increased focus on qualitative research to ensure patient input may help to better conceptualize and operationalize the variables most relevant to head and neck cancer surgery patients. In addition, the use of alternative methods of psychometric data analysis, such as Rasch, may improve the value of health measurement in clinical practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 60 publications
2
86
0
Order By: Relevance
“…Pusic et al (2007) in a systematic review of patient -reported outcome measures in head and neck surgery found that the EORTC QLQ-C30 was one of only three measures that fulfilled guidelines for instrument development and evaluation as outlined by the Medical Outcomes Trust.…”
Section: Methodsmentioning
confidence: 99%
“…Pusic et al (2007) in a systematic review of patient -reported outcome measures in head and neck surgery found that the EORTC QLQ-C30 was one of only three measures that fulfilled guidelines for instrument development and evaluation as outlined by the Medical Outcomes Trust.…”
Section: Methodsmentioning
confidence: 99%
“…8,[63][64][65][66] Also, comparing across studies is complicated by the different methods used to evaluate and define HRQOL. 67 Despite these difficulties, the population of patients with HNC needs to be included in the expanding evaluation of cancer survivorship issues for a number of rea- sons. First, it is frequently said and written that the survival of HNC has not improved for decades.…”
Section: Commentmentioning
confidence: 99%
“…ability to measure what it intends to measure) and responsiveness (e.g. capacity to identify changes in scores over time) cannot be assumed without their psychometric qualities being formally tested with child and adolescent burn patients [8].…”
Section: Introductionmentioning
confidence: 99%